1998
DOI: 10.1002/(sici)1097-0010(199801)76:1<91::aid-jsfa926>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary supplementation with Yucca schidigera extract or fractions thereof on nitrogen metabolism and gastrointestinal fermentation processes in the rat

Abstract: : Y ucca schidigera was fractionated with butan-1-ol, yielding a butanolextractable (BE) fraction, containing all the in vitro antimicrobial activity, and the aqueous, non-butanol-extractable (NBE) fraction. Four groups of Ðve female rats (12 weeks old) were allowed ad libitum access to diets supplemented with water (control) or 200 mg kg~1 total Y schidigera (TOT) or its fraction equivalent of NBE or BE for 64 days. The e †ects of the fractions and their interactions in the TOT treatment were analysed accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 17 publications
5
25
0
Order By: Relevance
“…Similar to the BUN differences in the current study, Caton et al (1988) observed an increase in BUN when providing a cottonseed-meal based supplement to forage fed lambs. As seen here, some reports show no effect on BUN when ruminants are supplemented with saponins (Wilson et al, 1998;Hristov et al, 1999), but more often it has been cited to reduce BUN (Hussain and Cheeke, 1995;Hussain et al, 1996;Killeen et al, 1998).…”
Section: Rumen Fermentation and Blood Urea Nitrogenmentioning
confidence: 56%
“…Similar to the BUN differences in the current study, Caton et al (1988) observed an increase in BUN when providing a cottonseed-meal based supplement to forage fed lambs. As seen here, some reports show no effect on BUN when ruminants are supplemented with saponins (Wilson et al, 1998;Hristov et al, 1999), but more often it has been cited to reduce BUN (Hussain and Cheeke, 1995;Hussain et al, 1996;Killeen et al, 1998).…”
Section: Rumen Fermentation and Blood Urea Nitrogenmentioning
confidence: 56%
“…Saponins (e.g., from Yucca schidigera) are proposed to reduce intestinal ammonia formation, and thus aerial pollution of housing environment, which is considered an important health stress, especially for young animals (Francis et al, 2002). Studies with rats confirmed the existence of active components in Y. schidigera extracts that lower intestinal urease activity and enzymes involved in the metabolic urea cycle (Killeen et al, 1998;Duffy et al, 2001). Reduced intestinal and fecal urease activities were also found in broilers fed such extracts (Nazeer et al, 2002).…”
Section: Specific Impact On Dietary Palatability and Gut Functionsmentioning
confidence: 99%
“…Reduced intestinal and fecal urease activities were also found in broilers fed such extracts (Nazeer et al, 2002). However, yucca extracts were reported to contain subfractions with partially antagonistic properties on intestinal urease activity and ammonia formation (Killeen et al, 1998). Thus, further research seems to be required to clarify the potential of saponins as feed additives for swine and poultry diets.…”
Section: Specific Impact On Dietary Palatability and Gut Functionsmentioning
confidence: 99%
“…Since Y. schidigera extract has become commercially available, a number of investigations into its effects on a wide range of animals have been carried out (Hussain et al, 1996;Hristov et al, 1999;Killeen et al, 1998a;Colina et al, 2001;Duffy et al, 2001;Flaoyen et al, 2002;Kaya et al, 2003). These studies have shown that the extract has many benefits on growth and performance of livestock (Mader and Brumm, 1987;Anthony et al, 1994;Balog et al, 1994;Cline et al, 1996) in particular it reduces gastrointestinal and fecal ammonia levels (Cheeke, 2000).…”
Section: Biological Activities Of Yucca Productsmentioning
confidence: 99%